2017
DOI: 10.1371/journal.pone.0170692
|View full text |Cite
|
Sign up to set email alerts
|

Static Posturography: A New Perspective in the Assessment of Lameness in a Canine Model

Abstract: The aim of this study was to assess the static posturography in dogs as a useful tool for diagnosis of lameness by means of the use of a pressure platform. For this purpose, a series of different parameters (pressure distribution, area of support, mean pressure, maximum pressure and statokinesiograms) were obtained from five lame dogs with unilateral elbow osteoarthritis treated with plasma rich in growth factors. Data were obtained before and 3 months after treatment, and results were compared with a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 36 publications
5
56
0
Order By: Relevance
“…Compared with humans, this study with dogs reflects great differences in statokinesiograms, since the ellipse that contains COP migrations revealed a dominant laterolateral orientation as previously reported [ 19 ], whilst, in bipedal support of human species, the ellipse has its longer axe in the antero-posterior sense [ 35 ]. This fact could be explained because quadupedy in dogs implies in the stance a bigger distance between limbs in the craniocaudal axis than the laterolateral and, thus, a greater stability in the longitudinal sense.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Compared with humans, this study with dogs reflects great differences in statokinesiograms, since the ellipse that contains COP migrations revealed a dominant laterolateral orientation as previously reported [ 19 ], whilst, in bipedal support of human species, the ellipse has its longer axe in the antero-posterior sense [ 35 ]. This fact could be explained because quadupedy in dogs implies in the stance a bigger distance between limbs in the craniocaudal axis than the laterolateral and, thus, a greater stability in the longitudinal sense.…”
Section: Discussionmentioning
confidence: 51%
“…At the moment of redaction for the present study, only a report dealing with statokinesiography in dogs [ 19 ] has been found; on the other hand, pedobarographic studies are very scarce and limited to static recordings [ 20 , 24 , 30 ]. In contrast, multiple publications can be found regarding these techniques in human medicine, rehabilitation, and sport fields [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations